Financial Frictions and Foreign Direct Investment: Evidence from Japanese Microdata - Horst Raff; Michael Ryan; Frank Stähler (Kiel Centre for Globalization (KCG), 2018)
Using Japanese microdata for the period 1980 to 2000 we find evidence for two transmission channels from financial shocks to foreign direct investment: a collateral channel, whereby changes in the value of investors' landholdings affect their borrowing ability; and a lending channel, whereby changes in bank health affect banks' lending ability. Decreasing land values by 55% on average from their peak in 1990 to the sample mean reduces the predicted number of investments by 17%. Reducing banks' market-to-book ratios by an average 61% from their high in 1986 to the sample mean lowers predicted investment counts by 21%.
Keywords: F23; L20; 330; Foreign direct investment; multinational enterprise; credit rationing; collateral; bank health; Japan